Determination of lipids and fatty acids in infant formula: comparison of the conventional x direct method - Kus-Yamashita, Mahyara Markievicz Mancio; Aued-Pimentel, Sabria; Mancini-Filho, Jorge (Revista do Instituto Adolfo Lutz, 2022)
Lipids in food are conventionally analyzed in two stages: extraction with organic solvent and fat esterification reaction, in this case, the type of fat of each food influences the choice of extraction and esterification reagents. In the direct method, such procedures are performed in one step. This work compared the conventional extraction method and quantification of lipids and fatty acids, with a direct method in infant formula. A reference sample of infant formula conteining certified lipids and fatty acids values from the National Institute of Standards and Technology was used. The conventional method for lipid analysis used the acid hydrolysis method; for the determination of fatty acids, the fats were extracted with a mixture of ethyl ether and petroleum ether. The direct method consisted of direct trans esterification with sodium methoxide. In the analysis of fatty acids, the majority of the results showed statistically equal values (α < 0.05) for both methods. The direct method proved suitable, mainly because of reduction in analytical time and quantity of solvents.